An Analysis of Mainland Chinese visitors' Motivations to visit Hong Kong - Cheung, Christina (2006)
Hong Kong, with its high quality and wide variety of visitor attractions and facilities, is one of the most popular destinations in Asia. In the past years, UK, USA, Japan, and Taiwan dominated Hong Kongs inbound markets. With the economic boom in China, there has been an amazing growth of visitors from China to Hong Kong over the past 13 years. The total number of tourist arrivals from China has increased more than ten times from 215,000 in 1984 to 2,311,000 in 1997 with an annual growth rate of 22.8%. In 1997, China accounted for 22% of the total tourist arrivals in Hong Kong, Hong Kong Tourist Association (Hong Kong Tourist Association, 1997). In 2006, the Labour Day 'golden week' (first week of May) saw the arrival of 387,615 mainland visitors to Hong Kong in the nine days to Sunday, the Immigration Department said. This was an increase of almost 5.2 per cent on the same period last year, which saw 368,465 mainland arrivals (Eng, D., 2006). The year-on-year increase in 2005 was 3.82 per cent from a year earlier. A total of 354,904 mainlanders visited Hong Kong in 2004 (Eng, D., 2006), the first full year that mainlanders could come as individual travellers under a scheme which was introduced in mid-July 2003, following the Sars outbreak. The importance of the Chinese market to the overall tourism industry in Hong Kong has drawn scholars interests in understanding what motivates them to travel overseas. The purpose of this study is: to identify motivations of Chinese travellers by adopting the push and pull factors as a conceptual framework. Deliberations of the hypothesis were cross examined through varying media to deduce a justifiable conclusion for the research.